2008
DOI: 10.2320/matertrans.ma200807
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hydrogen Storage Properties of a Single-Phase Magnesium Borohydride Mg(BH<SUB>4</SUB>)<SUB>2</SUB>

Abstract: A single phase Mg(BH 4 ) 2 was successfully synthesized and its hydrogen storage properties were systematically investigated. Depending on the synthesis conditions, Mg(BH 4 ) 2 forms low-and high-temperature phases with different crystal structures. The dehydriding reaction of Mg(BH 4 ) 2 starts at approximately 500 K, and 14.4 mass% of hydrogen is released through a multi-step reaction. Furthermore, 6.1 mass% of hydrogen can be rehydrided for the sample of Mg(BH 4 ) 2 after the dehydriding reaction, through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…So far, enthalpy change of 57 kJ mol À1 H 2 was reported for the reactions (a)+(b) (from Mg(BH 4 ) 2 to MgH 2 ), based on the PCT measurement. 9,12) The value is different from that determined from the first-principles calculations, 13) as shown in Table 1. Experimentally, Differential Scanning Calorimetry (DSC) measurement under hydrogen pressures can provide accurate values of enthalpy changes for dehydriding reactions.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…So far, enthalpy change of 57 kJ mol À1 H 2 was reported for the reactions (a)+(b) (from Mg(BH 4 ) 2 to MgH 2 ), based on the PCT measurement. 9,12) The value is different from that determined from the first-principles calculations, 13) as shown in Table 1. Experimentally, Differential Scanning Calorimetry (DSC) measurement under hydrogen pressures can provide accurate values of enthalpy changes for dehydriding reactions.…”
Section: Introductionmentioning
confidence: 71%
“…2 in the reaction (a). 9,[11][12][13] Further studies on Mg(BH 4 ) 2 are highly required viewpoints both from thermodynamics and dynamics aspects.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…1) In contrast to the compressed hydrogen and the liquefaction hydrogen, hydrogen storage in the solid state is the most promising alternative. [2][3][4][5] In the past decades, the complex hydrides consisting of light elements, e.g., alanates, [6][7][8][9][10] amides, [11][12][13][14][15] borohydrides [16][17][18][19][20] and ammonia borane (AB), [21][22][23] have been attracting extensive attention as the potential hydrogen storage materials due to their high gravimetric and volumetric hydrogen storage densities. In particular, significant efforts have been made in recent years with metal amide-hydride combined systems since Chen et al reported that lithium nitride, Li 3 N could absorb/desorb reversibly 11.4 mass% of hydrogen in 2002.…”
Section: Introductionmentioning
confidence: 99%